Bevacizumab prevents brain metastases formation in lung adenocarcinoma - Ilhan-Mutlu, Aysegül; Osswald, Matthias; Wick, Wolfgang; Winkler, Frank (Molecular cancer therapeutics, 2016)
Patients with nonsquamous non-small cell lung cancer (nsNSCLC; largely lung adenocarcinoma) are at high risk of developing brain metastases. Preclinical data suggested that anti-VEGF-A therapy may prevent the formation of nsNSCLC brain metastases. Whether non-brain metastases are also prevented, and whether bevacizumab shows a brain metastases-preventive activity in cancer patients is unknown. Data of one nsNSCLC (stage IIIB/IV, AVAiL) and two breast cancer bevacizumab trials (HER2 negative, AVADO; HER2 positive, AVEREL) were retrospectively analyzed regarding the frequency of the brain versus other organs being the site of first relapse. For animal studies, the outgrowth of PC14-PE6 lung adenocarcinoma cells to brain macrometastases in mice was measured by intravital imaging: under control IgG (25 mg/kg) treatment, or varying doses of bevacizumab (25 mg/kg, 2.5 mg/kg, 0.25 mg/kg). Brain metastases as site of first relapse were significantly less frequent in the bevacizumab arm of the AVAiL trial (HR = 0.36, P < 0.001). In AVADO and AVEREL, no significant difference was seen. In mice, bevacizumab treatment led to secondary regressions of non-brain macrometastases, but did not reduce their total incidence, and did not improve survival. In a brain-seeking nsNSCLC metastasis model, treatment with bevacizumab inhibited brain metastases formation, which resulted in improved overall survival. In summary, bevacizumab has the potential to prevent brain metastases in nsNSCLC, but no preventive activity could be detected outside the brain. These data indicate that anti-VEGF-A agents might be particularly relevant for those stage III nsNSCLC patients who are at high risk to develop future brain metastases. Mol Cancer Ther; 15(4); 702-10. ©2016 AACR.